Islamic Studies Update: Examining the Sharia Court in Aceh in the Perspective of Legislation in Indonesia - Ulum, Miftahul; Faizatul Muazzaroh; Mahmudah, Mahmudah; Ifdlolul Maghfur; Ahmad, Ahmad (UIN Sunan Gunung Djati Bandung, 2024)
The integration of Islamic law into Indonesia's national legal system continues to provoke significant constitutional and institutional discourse, particularly in the case of Aceh's Sharia Court (Mahkamah Syariah). Established under the special autonomy granted by Article 18 B of the 1945 Constitution, the court implemented Qanun Jinayat, an Islamic criminal code that operates within the national legal framework. This unique judicial structure highlights Indonesia's commitment to legal pluralism, while simultaneously exposing tensions between Islamic norms, human rights principles, and national legislative coherence. This study examined the legal status, institutional authority, and normative functions of the Syaria Court through the lens of constitutional law and legal pluralism. It adopts a normative legal research methodology that combines deductive reasoning, historical analysis, and case studies, and is supported by statutory documents, judicial rulings, and relevant literature. By framing the court as a hybrid institution shaped by regional autonomy and national oversight, this article offers a conceptual model of functional recognition, rather than hierarchical subordination. The findings reveal that Mahkamah Syaria exercises jurisdiction over both civil and criminal matters based on Islamic law. However, challenges remain in harmonising procedural standards, ensuring legal certainty, and accommodating plural citizenship, particularly in cases involving non-Muslim minorities. Despite these tensions, courts play a growing role in mediating religious legal traditions and constitutional imperatives. This article contributes to the broader academic discourse on judicial hybridity in decentralised states. It provides a new perspective on the adaptive function of religious courts within democratic legal systems, and proposes pathways for strengthening integration without eroding institutional pluralism.